1999
DOI: 10.1108/01443579910271700
|View full text |Cite
|
Sign up to set email alerts
|

Flexible kanban system

Abstract: Just-in-time (JIT) systems were originally designed for deterministic production environments such as constant processing times and smooth and stable demand. However, once implemented, JIT is fraught with numerous types of uncertainties, including variations in processing time and demand, planned interruptions such as preventive maintenance and unplanned interruptions such as equipment failure. These uncertainties lead to lowered production throughput, decreased machine utilization, increased order completion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…Several modified kanban methodologies were developed to deal with demand variability while preserving the advantages of traditional kanban system. Gupta and Al-Turki [19,20,21] and Gupta et al [22] proposed the concept of the flexible kanban system (FKS) in various environments involving uncertainties and interruptions. They demonstrated that in such environments, FKS outperforms the traditional kanban system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several modified kanban methodologies were developed to deal with demand variability while preserving the advantages of traditional kanban system. Gupta and Al-Turki [19,20,21] and Gupta et al [22] proposed the concept of the flexible kanban system (FKS) in various environments involving uncertainties and interruptions. They demonstrated that in such environments, FKS outperforms the traditional kanban system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Louis and Raymond [8] purposed that Kanban should be designed and adapted to implement in the proper way in accordance with each environment. Gupta et al [9] proposed a Flexible Kanban System (FKS) to handle random interruption in the production process. Several examples were carried out to compare the performances of this FKS policy with respect to the traditional JIT system and found this new system can outperform the traditional JIT system in all the cases considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Flexible Kanban System (FKS) was first introduced by Gupta, Al-Turki, and Perry (1999). They introduced this new system to cope with uncertainties and planned/unplanned interruptions.…”
Section: Overview Of Kanban Control Systems (Kcs)mentioning
confidence: 99%